Membagun Kepercayaan dan Saling Memahami Antar Anggota Organisasi di Restoran Greet Bear Bowl - Romana Rinda Nazara; Reydel Beginsa Lahagu; Sadaria Zebua; Siti Anggraini; Mardiana Halawa; Bayu Teta (Jurnal Rimba Riset Ilmu manajemen Bisnis dan Akuntansi, 2025)
This study aims to analyze the importance of building trust and mutual understanding among organizational members to enhance team performance and work effectiveness at Greet Bear Bowl Restaurant. Trust is developed through open communication, organizational justice, and recognition of individual contributions. Meanwhile, mutual understanding is supported by active participation, aligned goals, and a positive organizational culture. The study adopts a qualitative approach using in-depth interviews with four permanent employees. The results indicate that trust and understanding play a crucial role in strengthening work relationships, improving coordination, and supporting the effective and sustainable achievement of organizational goals.